2007
DOI: 10.1083/jcb.200702143
|View full text |Cite
|
Sign up to set email alerts
|

A novel insertion pathway of mitochondrial outer membrane proteins with multiple transmembrane segments

Abstract: The central channel Tom40 of the preprotein translocase of outer membrane (TOM) complex is thought to be responsible for the import of virtually all preproteins synthesized outside the mitochondria. In this study, we analyze the topogenesis of the peripheral benzodiazepine receptor (PBR), which integrates into the mitochondrial outer membrane (MOM) through five hydrophobic transmembrane segments (TMSs) and functions in cholesterol import into the inner membrane. Analyses of in vitro and in vivo import into TOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 24 publications
9
68
0
1
Order By: Relevance
“…In contrast, results from other groups (46,47) show that deletion or depletion of TOM70, TOM20, and TOM22 affects mitochondrial import of pSU9/DHFR. However, we did not observe significant inhibition of mitochondrial import of this protein in tom70⌬ and tom22⌬ cells under either in vivo (Fig.…”
Section: Targeting Of Cyp Proteins To Mitochondria In Intact Cellsmentioning
confidence: 51%
“…In contrast, results from other groups (46,47) show that deletion or depletion of TOM70, TOM20, and TOM22 affects mitochondrial import of pSU9/DHFR. However, we did not observe significant inhibition of mitochondrial import of this protein in tom70⌬ and tom22⌬ cells under either in vivo (Fig.…”
Section: Targeting Of Cyp Proteins To Mitochondria In Intact Cellsmentioning
confidence: 51%
“…For example, proteins containing a presequence are imported in a Tom20-dependent manner, whereas carrier proteins and proteins containing multiple ␣-helical transmembrane segments are imported in a Tom70-dependent manner. Moreover, ␤-barrel proteins are integrated into the mitochondrial outer membrane by the cooperation of Tom20-and Tom70-dependent processes (32,57). Using immunoprecipitation in the presence of a crosslinker and with Tom20 and Tom22 under native conditions, Lazarou et al reported that PINK1 interacts with Tom20, Tom22, Tom40, and Tom70 (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the identified MTS of APE1 in the present study is located in the C terminus, which is more similar to tailanchored preproteins. The mitochondrial tail-anchored preproteins, including Bcl-2 and Tom20, were inserted into the mitochondrial outer membranes via a C-terminal transmembrane domain (28,29). Although the exact localization of APE1 in the mitochondria has not been well characterized, according to its function in mitochondrial DNA repair, its distribution should accompany the mitochondrial DNA in the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%